2021
DOI: 10.7150/ijbs.59581
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mitochondrial transplantation therapy from different gender on inhibiting cell proliferation of malignant melanoma

Abstract: Today mitochondria are considered much more than a energy plant in cells. Mitochondrial transplantation therapy has been an active research area for treating mitochondria-associated diseases from animal studies to clinical trials. However, the specific mechanism involved in the anti-tumor activity of healthy mitochondria remain to be characterized. Here we investigate the signal mechanism and gender difference of mitochondrial transplantation therapy against malignant melanoma. In the study, we administrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
(53 reference statements)
0
19
0
1
Order By: Relevance
“…Inhibiting syncytin-1/2 by their antibodies almost completely suppressed mitochondrial uptake via the cancer cell membrane, reducing tumour drug resistance [188]. In addition, data from Yu et al suggested that mitochondrial transfer suppressed melanoma cell proliferation in vitro via cell cycle arrest and increased cell apoptosis [189]. Chang et al demonstrated that through mitochondrial coincubation or pep-1-mediated mitochondrial delivery, the progression of MCF-7 breast cancer cells was significantly inhibited; these MCF-7 breast cancer cells showed an increase in cell apoptosis and a decrease in cell proliferation.…”
Section: Cancermentioning
confidence: 99%
“…Inhibiting syncytin-1/2 by their antibodies almost completely suppressed mitochondrial uptake via the cancer cell membrane, reducing tumour drug resistance [188]. In addition, data from Yu et al suggested that mitochondrial transfer suppressed melanoma cell proliferation in vitro via cell cycle arrest and increased cell apoptosis [189]. Chang et al demonstrated that through mitochondrial coincubation or pep-1-mediated mitochondrial delivery, the progression of MCF-7 breast cancer cells was significantly inhibited; these MCF-7 breast cancer cells showed an increase in cell apoptosis and a decrease in cell proliferation.…”
Section: Cancermentioning
confidence: 99%
“…This further confirmed the feasibility of using MT to inhibit tumor growth. In addition, the antitumor activity of mitochondria in female mice was higher than that in male mice, which might be attributed to the fact that the mitochondria in female mice were more likely to induce mitochondria-nuclear communication 42 (Table 3).…”
Section: Successful Applications Of Mt In Diseasesmentioning
confidence: 99%
“…The PEP-1–mediated MT successfully weakened the viability of MCF-7 breast cancer cells, which was manifested by inhibiting cell proliferation, inducing caspase-mediated apoptosis, and improving the sensitivity of chemotherapy. Yu et al 42 used the intact mitochondria extracted from mouse liver to act on mice with malignant subcutaneous melanoma and with metastatic melanoma, respectively, and then compared the transfer efficiency of mitochondria in melanoma cells between female and male mice. The results showed that mitochondria could significantly inhibit the proliferation of tumor cells in vitro by blocking the cell cycle and inducing apoptosis.…”
Section: Successful Applications Of Mt In Diseasesmentioning
confidence: 99%
“…Defects in mitochondrial function are associated with disturbances in many intracellular physiological processes. 11,12 Today, mitochondrial therapy (mitotherapy) is considered a new strategy for the treatment of mitochondrial diseases. 13,14 The purpose of mitotherapy is to transfer exogenous healthy mitochondria into defective mitochondria in cells to prevent and improve mitochondrial diseases.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The purpose of mitotherapy is to transfer exogenous healthy mitochondria into defective mitochondria in cells to prevent and improve mitochondrial diseases. 12,15 Studies have shown that mitochondria can significantly improve mitochondrial dysfunction caused by various compounds. In in vivo and in vitro studies, the mitochondrial transfer is done by simple co-incubation in the culture system or by intravenous injection into animals.…”
Section: Introductionmentioning
confidence: 99%